Production improvement through the use quest simulation technique of layout optimization specific on labour optimization / Mohamad Sukri Mohamed Shamsudin - Mohamed Shamsudin, Mohamad Sukri (2010)
This paper presents a layout study that used simulation technique to improve plant layout of the factory floor Propoly (M) Sdn. Bhd which involved the production of plastic injection molding machine to produce platic part for automative industry. In this study, the main aspects are to simulate and analyze the current plant layout and then improvement layout will be proposed in order to optimize production rate of the finish good, space utilization, material storage and handling, and also meaning optimization. Finally, the performance of the new layout will be evaluated and compared with that current layout performance. By using Delmia Quest software as a tool it will be able to help to achieve the objective of this study. Delmia Quest is a complete 3D digital factory environment for process flow simulation and analysis, accuracy, and profitability. In additional quality control tools (QC 7 tools) method will be applied for this study as a guide line and reference in collecting data and problem solving analysis in order to obtain the optimum result base on plant layout at research location. As a key result from this study, the production improvement increases the labor utilization percentage and decreases labor idle time in the production system if the factory adopted the improved layout. From these studies, it can be conclude that, an optimum floor layout configuration can be obtained by using simulation technique in order to achieve the objective.